1992
DOI: 10.1111/j.1471-4159.1992.tb11012.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Several Cations on the Neuronal Uptake of Dopamine and the Specific Binding of [3H]GBR 12783: Attempts to Characterize the Na+ Dependence of the Neuronal Transport of Dopamine

Abstract: We have studied the effects of several cations on (1) the neuronal uptake of [3H]dopamine ([3H]DA) and (2) the specific binding of 1-[2-(diphenylmethoxy)ethyl]-4-(3-phenyl-2-[1-3H]propenyl)piperazi ne ([3H]GBR 12783) to a site associated with the neuronal carrier of DA, in preparations obtained from rat striatum. When studied under the same experimental conditions, both the uptake of [3H]DA and the binding of [3H]GBR 12783 were similarly impaired by the gradual replacement of NaCl by sucrose. In both processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 33 publications
8
44
0
Order By: Relevance
“…The present results did not indicate a preferential exclusion of partially or non-glycosylated DAT from the plasma membrane even though there was a tendency for less glycosylated material to be somewhat underrepresented in the surface fraction. In fact, the protein content of the surface fraction was reduced in the double and triple mutant compared with wild type to the same extent as that in the total fraction, consonant with the conclusion of Torres et (25)(26)(27). Taken together the data suggest that both non-glycosylated and mature DAT reaches the surface.…”
Section: Discussionsupporting
confidence: 86%
“…The present results did not indicate a preferential exclusion of partially or non-glycosylated DAT from the plasma membrane even though there was a tendency for less glycosylated material to be somewhat underrepresented in the surface fraction. In fact, the protein content of the surface fraction was reduced in the double and triple mutant compared with wild type to the same extent as that in the total fraction, consonant with the conclusion of Torres et (25)(26)(27). Taken together the data suggest that both non-glycosylated and mature DAT reaches the surface.…”
Section: Discussionsupporting
confidence: 86%
“…Inward transport could be blocked with 100 µM cocaine, and is dependent on Na ϩ and Cl -with reaction orders of 2 and unity, respectively. These results are in agreement with previously published studies (Krueger, 1990;Amejdki-Chab et al, 1992a;Wheeler et al, 1993) on the uptake of [ 3 H]dopa- mine into striatal preparations as well as those studies where nonradiolabeled dopamine was monitored (McElvain and Schenk, 1992;Povlock and Schenk, 1997). In HEK hDAT cell suspensions, [Na ϩ ] or [Cl -] reduction decreases the V max and increases the K m for dopamine inward transport (Fig.…”
Section: Comments On the Ability Of Hek Hdat Cells To Inwardly Transpsupporting
confidence: 94%
“…On the other hand, increasing [NaCl] from 50 to 134 mM enhanced the ability of DAT substrates dopamine and amphetamine to displace [ 125 I]RTI-121. With a similar buffer system at 0°C, Bonnet et al (1990) reported that uptake blockers (mazindol, nomifensine, methylphenidate, and cocaine) and substrates (DA and amphetamine) were equipotent in their ability to compete with [ 3 H]GBR 12783 when [Na 1 ] was increased from its peak value, 10 mM, to 130 mM (Amejdki-Chab et al, 1992b;Benmansour et al, 1987). With A Ringer medium containing 140 mM NaCl at 4°C, Maurice et al (1991) noticed that the abilities of DA and amphetamine to displace [ 3 H]BTCP were greatly increased compared with a 50-mM phosphate buffer.…”
Section: Discussionmentioning
confidence: 97%